The Effect of Principals’ Leadership and Learning Organization on Teachers’ Innovative Work Behavior During the COVID-19 Pandemic - Hidayat, Rais; Patras, Yuyun Elizabeth (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2022)
This research explores evidence of the conceptual model related to principals' leadership, learning organization, and teachers' innovative work behavior during the COVID-19 pandemic. This research applied a survey method in which participants employed selections through the purposive sampling technique. There were 1243 respondents in this sample. Subsequently, 1200 were then used to elicit further data. The data collection procedure was carried out online by distributing questionnaires to teachers in Indonesia via the Google Form application. The questionnaire was made based on theoretical studies, expert judgments, and readability assessments, where the analysis of research data employs the so-called path analysis with SMART PLS. The findings of this research evidence the following cases. First, principals' leadership has a positive and significant direct influence on teachers' innovative work behavior. Second, principals' leadership has a positive and significant direct influence on learning organizations. Third, learning organization has a positive and significant direct influence on the teachers' innovative work behavior. Fourth, principals' leadership through learning organization has a positive and significant indirect influence on the teachers' innovative work behavior. These findings support the notion that is improving teachers' innovative work behavior, especially during the COVID-19 pandemic, requires improvement of principals' leadership and the learning organization.